Perspectivas dos impactos socioeconômicos do complexo eólico canoas e lagoas - Costa, Isis dos Santos (Universidade Federal Rural do Semi-Árido, 2018)
The search for alternative sources of energy has been rising in the world at home from environmental and economic concerns. In this context, the various nations of the world are looking for alternatives that can address such concerns. Wind energy is one of the forms of renewable energy that has been used the most, and the Brazilian Northeast deserves to be highlighted in this issue, since it has become one of the main concentrating regions of projects in this sector. Known for its strong solar irradiance and high temperatures, the region located in the interior of the state of Paraíba, known as Seridó paraibano, has recently been discovered as a great source of wind energy. The Brazilian Wind Power (FEB) has discovered a potential for wind power and has implemented a wind farm called Canoas e Lagoas, with three wind farms: Lagoa I and II and Canoas, consisting of a total of 45 wind farms located in the rural areas of the municipalities of Santa Luzia, São José do Sabugí and Junco do Seridó. In this sense, the study approaches approaches in the area of the wind sector, and from what has been mentioned, the objective of this study is to evaluate the perspectives regarding the socioeconomic impacts caused by the construction of the wind farms in the mentioned cities, aiming to verify the expectations of job creation that the region's residents expect, as well as the improvement of the economy in the locality, as well as to investigate what the local commerce expects for its business with the implantation of the wind farms, mainly with regard to the food and real estate. For the accomplishment of this work, a bibliographical review and field trip is carried out, in which questionnaires are applied that seek to collect the opinions of the population of the studied municipalities. In this way, it was verified that the FEB enterprise generated positive social and economic impacts in the region, where it was possible to verify the way in which people were benefited, as well as the diverse opinions regarding good socioeconomic expectations.
Artigo Acadêmico
Keywords: Energia eólica; Expectativas; Impactos socioeconômicos; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA